The culturally conscious board setting the boardroom table for impact - Jukanovich, Jennifer M.; West, Russell W. (Ascent Audio, 2024)
The definitive introduction for changemakers new to the world of nonprofit and small business boards of directors. Bust the status quo of board room administrative tedium and passive participation to contribute to meaningful social transformation and impact in your organization. Authors Jukanovich and West offer changemakers new to the boardroom the mindset and strategies necessary to make a difference in the organizations they lead. Mission-based, socially responsible, and transformational organizations are needed more today than ever. And the boards that lead them must be in tune with their stakeholder's culture. But so often they are held back by ineffective decision making and a lack of interpersonal trust. This book breaks down the key elements of a successful boardroom and how to achieve them. From onboarding diverse talent to establishing trust through accountability, you will have the tools and actionable techniques needed to effectively make a difference in the world with healthier boardroom practices.
Online resource; title from title details screen (O'Reilly, viewed October 22, 2024)
Keywords: Boards of directors; Multiculturalism; Conseils d'administration; Multiculturalisme; multiculturalism; Audiobooks; Livres audio